Intraocular magnet of Parel. Issue 12 (December 1986) - Crock, G. W.; Janakiraman, P.; Reddy, P.
Abstract : The intraocular magnet (IOM) is a new device based on permanent magnetism providing controlled energy for removal of magnetic intraocular foreign bodies. Its use is reported in 11 cases.